The main features of Ukrainian speech etiquette - Жук (Лаврик), Дар’я Сергіївна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”)
This article discovers peculiarities of Ukrainian speech etiquette, deals with the term «speech etiquette» and different ways of it nomination by scientists. The existence of interdependence between the speech etiquette units with mentality of Ukrainian people was uncovered. This paper focuses on lingual cultural maternal code as a dominant thing for Ukrainian nation. Using poetic works for children the author singled out the most widespread etiquette units in speech of Ukrainians. There was analyzed the language means, maximally describing the notion «lingual cultural maternal code».